Pengaruh Kepuasan Terhadap Loyalitas pada Pembelian Produk Fashion Muslim Melalui Marketplace Shopee - Yudha Trishananto (Journal of Applied Islamic Economics and Finance, 2021)
This research aims to understand the effect of consumer satisfaction on loyalty through trust as an intervening variable in purchasing Muslim Fashion products through the shopee market place. Steps to collect data with the help of a questionnaire through an interval scale. The sample obtained is 100 respondents through purposive sampling technique. The data is then processed through SmartPLS, analyzed through convergent validity, discriminant validity, composite reliability, average variance extracted (AVE), collinearity statistics (VIF), path coefficient test, goodness of fit test, hypothesis testing with bootstrap, then test moderation through SEM. Hypothesis testing on the satisfaction variable found a positive and significant effect on hedonic shopping value and utilitarian value. The trust variable has a positive and significant effect on hedonic shopping value and utilitarian shopping value. The satisfaction variable was found to have a positive effect on trust. The trust variable has a positive effect on loyalty and the satisfaction variable has no effect on loyalty. The satisfaction variable was found to have an effect on loyalty through trust.